2011
DOI: 10.1158/1078-0432.ccr-10-2234
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations from the iSBTc-SITC/FDA/NCI Workshop on Immunotherapy Biomarkers

Abstract: Purpose: To facilitate development of innovative immunotherapy approaches, especially for treatment concepts exploiting the potential benefits of personalized therapy, there is a need to develop and validate tools to identify patients who can benefit from immunotherapy. Despite substantial effort, we do not yet know which parameters of antitumor immunity to measure and which assays are optimal for those measurements.Experimental Design: The iSBTc-SITC (International Society for Biological Therapy of Cancer-Soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
151
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(155 citation statements)
references
References 79 publications
3
151
0
Order By: Relevance
“…Finally, the different classes of biomarkers that are relevant to T-cell therapy trials have to be identified (Lacey et al, 2013). Accordingly, a CAR-T-19 cell clone was engineered for adoptive therapeutic use against cancer, and there is increasing interest in identification of sensitive, robust, and meaningful biomarkers that may provide relevant insights into the clinical development process Butterfield et al, 2011).…”
Section: Biomarkers and Symptomatologymentioning
confidence: 99%
“…Finally, the different classes of biomarkers that are relevant to T-cell therapy trials have to be identified (Lacey et al, 2013). Accordingly, a CAR-T-19 cell clone was engineered for adoptive therapeutic use against cancer, and there is increasing interest in identification of sensitive, robust, and meaningful biomarkers that may provide relevant insights into the clinical development process Butterfield et al, 2011).…”
Section: Biomarkers and Symptomatologymentioning
confidence: 99%
“…Assays for quantifying vaccinespecific and/or vaccine-induced responses mainly include DTH, multimer staining for MHC-tumor peptide, cytotoxicity, T-cell proliferation assays, ELISA for tumor protein-specific antibodies and ELISPOT assays that detect IFN-g producing T cells. Analysis of immune cell subsets from PBMCs has recently been performed in some studies including, in addition to T-cell and antibody responses, quantitation of Tregs, MDSCs, NK cells and DCs [22,78,79]. Most of these assays are being studied in different clinical trials and in many cases the detected immunological response was associated with improved clinical outcomes [22,32,80].…”
Section: Clinical Considerationsmentioning
confidence: 99%
“…Some trials have analysed also the antibody response to TAA, or variations in the percentage of Treg, myeloid derived suppressor cells, NK and DCs, often evaluating the ratio of effector to regulatory cells. In addition, many studies have used analysis of multiple serum cytokines and chemokines [3,[93][94][95][96][97][98].…”
Section: Immune Monitoring For Cancer Immunotherapymentioning
confidence: 99%
“…Some trials have analysed also the antibody response to TAA, or variations in the percentage of Treg, myeloid derived suppressor cells, NK and DCs, often evaluating the ratio of effector to regulatory cells. In addition, many studies have used analysis of multiple serum cytokines and chemokines [3,[93][94][95][96][97][98].The study from Di Nicola et al, for example, documented significant changes in Treg, NK and anti-tumor T-cell frequencies, and humoral responses in responding patients compared with non-responding ones. These observations indicate that the clinical responses observed after tumor-loaded DC-based vaccination may be the result of an active modulatory effect on different components of the immune system [55].…”
mentioning
confidence: 99%